Peran Price Earning Ratio Sebagai Pemoderasi Hubungan antara Leverage dan Profitabilitas Terhadap Harga Saham Perusahaan sektor Teknologi pada Tahun 2021 dan 2022 - Rahmania Mustahidda; Maulana Ihsan Yusufi Suyatno; Anisa Kusumawardani (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The purpose of this research are determine to (1) the influence leverage which is notated withDebt Equity Ratio and profitability which is denoted byReturn On Equity to share prices. (2) Role of Price Earning Ratio in moderating the between Debt Equity Ratio and Return On Equity into stock prices. The research object is technology sector companies listed on the Indonesia Stock Exchange during 2021 and 2022. Was conducted using the SmartPLS tool with results (1)Debt Equity Ratio (THE) has a significant negative influence on stock prices (2)Return On Equity (ROE) has a significant positive influence on stock prices (3)Price Earning Ratio (PER) can’t moderate the influence Debt Equity Ratio to the stock price. (4)Price Earning Ratio (PER) can moderate the influenceReturn On Equity to the stock price.